2009
DOI: 10.1007/s11187-009-9177-7
|View full text |Cite
|
Sign up to set email alerts
|

Firm size, age, industrial networking, and growth: a case of the Korean manufacturing industry

Abstract: Firm growth, Industrial networking, Subcontracting, Clustering, Korean manufacturing industry, L14, L25, L26, L52, L60, O25,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 61 publications
2
59
1
4
Order By: Relevance
“…The finding showed that size, level of activity and those provisions of collateral are very significant in the capital structure of different Irish SMEs. Park, et al (2010) highlighted the role of size of SMEs and industrial networking in determining SME growth. An analysis of many Korean SMEs in different sectors between 1994 and 2003 confirmed that size has an important negative impact on SMEs.…”
Section: Size Of Smesmentioning
confidence: 99%
“…The finding showed that size, level of activity and those provisions of collateral are very significant in the capital structure of different Irish SMEs. Park, et al (2010) highlighted the role of size of SMEs and industrial networking in determining SME growth. An analysis of many Korean SMEs in different sectors between 1994 and 2003 confirmed that size has an important negative impact on SMEs.…”
Section: Size Of Smesmentioning
confidence: 99%
“…Apart from that, although researches by Tsai and Goshal (1998) and Casson and Giusta (2007) have repeatedly discussed the importance of networks in promoting entrepreneurship, there is not much literature concerning the contribution of networks linked to business sustainability (Tsai and Goshal, 1998). Even if there are studies on entrepreneurship and network, it is limited to a single industry (Schilling and Phelps, 2007) and the manufacturing industry is the favorite (Park, Shin and Kim, 2010).…”
mentioning
confidence: 99%
“…Young/small businesses are more sensitive to the cycle than older/larger businesses. Also Park et al (2010) confirm that firm size and age have significant negative effects on firm growth and significant positive impacts on firm survival. We use net sales as a proxy for firm size and when compared with other metrics of firm size like assets, nº of employees and market capitalization, according to Dang et al (2018) sales are more related to product market which is relevant to measure market share, endurance of the product and life cycle stage.…”
Section: Resultsmentioning
confidence: 53%